2022
DOI: 10.3389/fimmu.2022.1015128
|View full text |Cite
|
Sign up to set email alerts
|

Complement C1s as a diagnostic marker and therapeutic target: Progress and propective

Abstract: The molecules of the complement system connect the effectors of innate and adaptive immunity and play critical roles in maintaining homeostasis. Among them, the C1 complex, composed of C1q, C1r, and C1s (C1qr2s2), is the initiator of the classical complement activation pathway. While deficiency of C1s is associated with early-onset systemic lupus erythematosus and increased susceptibility to bacteria infections, the gain-of- function variants of C1r and C1s may lead to periodontal Ehlers Danlos syndrome. As C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 89 publications
0
16
0
Order By: Relevance
“…However, complement analysis in pEDS patients does not usually show any abnormalities ( 4 ), and beyond activation of the complement components C4 and C2, C1s has been shown to act on wide range of cellular protein and regulatory pathways ( 12 ). There is no evidence that C4 is indeed the main target of activated C1s outside the C1 complex in vivo , and uncontrolled production of aC1s may have various complement-independent effects depending on the molecular availability of other substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, complement analysis in pEDS patients does not usually show any abnormalities ( 4 ), and beyond activation of the complement components C4 and C2, C1s has been shown to act on wide range of cellular protein and regulatory pathways ( 12 ). There is no evidence that C4 is indeed the main target of activated C1s outside the C1 complex in vivo , and uncontrolled production of aC1s may have various complement-independent effects depending on the molecular availability of other substrates.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested a variety of biological functions of C1s beyond its role in complement activation ( 12 ). In 1990, Yamaguchi and colleagues reported that aC1s may proteolytically cleave collagens I and II in an in vitro assay ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that abnormal activation of C1S contributes to the development of autoimmune and infectious diseases. In addition, the overexpression of C1S may be a new escape mechanism to promote tumor progress (54). CASP4, as a gene related to cell apoptosis, is differentially expressed in a variety of tumors, and can be used to predict the prognosis of tumor patients (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…This study therefore focuses on how free complement C1s protease cleaves HMGB1 and how this could impact HMGB1 inflammatory cytokine signaling. This is interesting because activated C1s is found in some specific disease contexts such as SLE (48) but also in other autoimmune and cancer disease contexts (49)(50)(51). At present, it is not known if this pathological activated C1s is in a free form or not, but it likely escapes from the functional control of C1q and C1-INH.…”
Section: Vertebrate Immune Defense and Homeostasis Rely On Several Al...mentioning
confidence: 99%